PROBLEMATIKA EKSISTENSIAL PENDIDIKAN HUMANIORA BERBASIS MEDIA TEKNOLOGI DIGITAL SECARA DARING - Sihotang, Kasdin (Sapientia Humana: Jurnal Sosial Humaniora, 2021)
Education is a path of humanization and hominization. Through education the subject develops multidimension of human being in order to be more human. The development of multidimensional humanity is existentially taking place through personal encounters between educators and students. But Covid 19 has changed all that. The essence of education based on personal and direct relationships between educators and students is considered threating, because it can become a new cluster in the spread of Covid 19. Therefore, the form of teaching that is considered appropriate is online-based learning. This learning model does not prioritize direct relationships, but rather relationships mediated by technology. This form of relationship certainly has two sides. On the one hand, the use of digital technology helps reduce the anxiety of parents, while helping the government overcome the spread of virtues. But on the other hand, it is also necessary to look at the fundamental problems that are present behind the use of digital technology. The fundamental problem concerns several things: first, the elimination of educational values as a form of co-living characterized by interpersonal relationships. Second, the problem of justice, be it commutative justice and legal justice that supposes the availability of technology equally and adequately as a means of use, but in reality, is not. The third, the formation of digitally characterized human being, that are heteronomy, passive attitudes, and absolute dependence.